Analisis Penguasaan Konjugasi Kata Kerja Bahasa Jerman - Devilia, Kaila; Jufri, Jufri; Hasmawati, Hasmawati (Academic : Journal of Social and Educational Studies, 2025)
Abstract. This research aims to collect data and information about the German verb conjugation skills of class XII SMAN 8 Gowa and the factors that influence it. This research uses a quantitative method with a descriptive approach. The population in this study consisted of three classes, namely IPS 1, IPS 2, and IPS 3 with a total of 106 students. The sample was taken by stratified random sampling. The sampe consisted of 30 students, with 10 students taken from each of the three classes. The data was collected through an objective in the form of a fill-in-the-blank test, while to find out the factors that influence it, a closed questionnaire was used. The research data were analyzed using percentage techniques. The students mastery of conjugation in weak verbs (schwache Verben) is 77% in the good category, strong verbs (starke Verben) is 47% in the almost sufficient category, and modal verbs (Modalverben) is 78,7% in the good category. Based on the data analysis, it is concluded that the final result of the German verb conjugation mastery of class XII SMAN 8 Gowa is more than sufficient (67,43%). The factors that influence it consist of supporting and inhibiting factors, which are each divided into internal and external factorsKeywords: Mastery analysis, Verb Conjugation, Influencing factors, German